2018
DOI: 10.1364/ao.57.001874
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of image reconstruction techniques for optical projection tomography

Abstract: We present a comparison of image reconstruction techniques for optical projection tomography. We compare conventional filtered back projection, sinogram filtering using the frequency-distance relationship (FDR), image deconvolution, and 2D point-spread-function-based iterative reconstruction. The latter three methods aim to remove the spatial blurring in the reconstructed image originating from the limited depth of field caused by the point spread function of the imaging system. The methods are compared based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Filtered back projection (FBP) algorithms are the most commonly used algorithm for OPT reconstruction . However, FBP algorithm cannot be fully applied to OPT reconstructions . It does not account for refraction, scattering and diffraction of the light .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filtered back projection (FBP) algorithms are the most commonly used algorithm for OPT reconstruction . However, FBP algorithm cannot be fully applied to OPT reconstructions . It does not account for refraction, scattering and diffraction of the light .…”
Section: Introductionmentioning
confidence: 99%
“…However, FBP algorithm cannot be fully applied to OPT reconstructions . It does not account for refraction, scattering and diffraction of the light . Moreover, to obtain high quality of reconstruction image, hundreds of projections are often required.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study compared several reconstruction techniques in fluorescence OPT 50 . They concluded that a reconstruction method based on point spread function analysis, which GBM and SGBM are, is good for nonsparse objects, such as the zebrafish embryo.…”
Section: Discussionmentioning
confidence: 99%
“…No aliasing sampling and quantization super-resolution reconstruction, these blurs are usually characterized by point spread functions [14]. (3) Sampling: the light emitted by the object is converted into an electric signal on the sensor.…”
Section: Continuous Scenementioning
confidence: 99%